PENGEMBANGAN INSTRUMEN PENGUKURAN IKLIM SEKOLAH BERBASIS WEB - Rahmania Utari; Adi Dewaanto; Mada Sutapa (Universitas Negeri Malang, 2019)
Abstract: This study aims to produce a product in the form of a web-based school climate information system. The design of this study uses a combination of research and development (R dan D) with design and development (D dan D). The development of a school climate information system involves various education stakeholders in Gunungkidul Regency, Yogyakarta Special Province, especially at the high school / vocational level and the equivalent. Based on the results of the trials conducted in two stages in two different schools in Gunungkidul Regency, the website-based school climate measurement information system is feasible to be used and applied especially at the high school and vocational level. The use of the school climate web can help school principals identify school situations and on the other hand school people are directly involved in the process of improving their schools by providing an assessment of their school climate. This system should be disseminated and disseminated to schools in a wider scope. However, there are special notes in terms of users, especially parents. Of all the elements of the user, parents have limited use of the website because of barriers to internet literacy and uneven access. Therefore, especially for parents, it is recommended that the use of this instrument be combined with manual instruments so that parents can still participate in measuring the school climate.Abstrak: Penelitian ini bertujuan menghasilkan menghasilkan produk berupa sistem informasi iklim sekolah berbasis web. Desain penelitian ini menggunakan kombinasi antara research and development (R dan D) dengan design and development (D dan D). Pengembangan sistem informasi iklim sekolah melibatkan berbagai stakeholder pendidikan di Kabupaten Gunungkidul Provinsi Daerah Istimewa Yogyakarta khususnya pada jenjang SMA/SMK dan yang sederajat. Berdasarkan hasil uji coba yang dilakukan dalam dua tahap di dua sekolah berbeda di Kabupaten Gunungkidul, sistem informasi pengukuran iklim sekolah berbasis website layak digunakan dan diaplikasikan khususnya pada tingkat sekolah menengah atas dan kejuruan. Pemanfaatan web iklim sekolah dapat membantu kepala sekolah mengidentifikasi situasi sekolah dan di sisi lain warga sekolah terlibat langsung dalam proses memperbaiki sekolahnya dengan memberikan penilaian tentang iklim sekolahnya. Sistem ini patut didiseminasikan dan disosialisasikan kepada sekolah-sekolah dalam lingkup yang lebih luas. Namun demikian terdapat catatan khusus dari segi pengguna khususnya orangtua. Dari kesemua unsur pengguna, orangtua memiliki keterbatasan dalam memanfaatkan website karena hambatan literasi internet dan akses yang belum merata. Oleh karena itu, khusus bagi kalangan orangtua, direkomendasikan agar penggunaan instrumen ini dipadukan dengan instrumen manual agar orangtua tetap dapat berpartisipasi dalam pengukuran iklim sekolah.